Gender Fluidity in Lengger Banyumasan: Interplay of Masculine and Feminine Elements in a Traditional Javanese Dance - Kholid Mawardi; Nurkholis (Asian Journal of Philosophy and Religion, 2024)
This study explores the intricate gender dynamics within the Lengger Banyumasan dance, a traditional performance art from Banyumas, Central Java. Known for its captivating fusion of masculine and feminine elements, the dance embodies fluid gender roles through movements, costumes, and interactions between performers. This research investigates how both male and female performers navigate and express gender identities, challenging conventional norms and highlighting the dance’s role in reflecting and shaping societal values. The findings contribute to understanding gender performativity within traditional arts, emphasizing Lengger Banyumasan's continued cultural relevance amidst modern influences.